2017
DOI: 10.5114/ada.2017.67076
|View full text |Cite
|
Sign up to set email alerts
|

Association between mean platelet volume and disease severity in patients with psoriasis and psoriatic arthritis

Abstract: IntroductionMean platelet volume (MPV) is an important marker that shows the activation and function of the platelets, which is effective in the inflammatory diseases.AimTo show the relationship between MPV and the development of psoriatic arthritis (PA) in patients with psoriasis vulgaris (PV) and the correlation between MPV and psoriasis severity score (PASI).Material and methodsOur study included 116 patients with psoriatic arthritis (68 female, 48 male) and 41 patients in the psoriasis group (19 female, 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“… 2 , 11 , 28 MPV and PDW are known as PLT activation indices, reflecting the PLT production rate and stimulation. 2 , 11 , 29 In the literature, there are contradictory results about the relationship between platelet activation markers and psoriasis. 2 , 27 , 29 , 30 In a study carried out in Korea, significantly higher MPV and PDW values were found in patients with psoriasis than in controls and a positive correlation was observed between MPV and PASI score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 11 , 28 MPV and PDW are known as PLT activation indices, reflecting the PLT production rate and stimulation. 2 , 11 , 29 In the literature, there are contradictory results about the relationship between platelet activation markers and psoriasis. 2 , 27 , 29 , 30 In a study carried out in Korea, significantly higher MPV and PDW values were found in patients with psoriasis than in controls and a positive correlation was observed between MPV and PASI score.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 11 , 29 In the literature, there are contradictory results about the relationship between platelet activation markers and psoriasis. 2 , 27 , 29 , 30 In a study carried out in Korea, significantly higher MPV and PDW values were found in patients with psoriasis than in controls and a positive correlation was observed between MPV and PASI score. 11 In contrast, Saleh et al 31 reported that there was no significant difference in MPV levels between patients with psoriasis and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Vaya et al indicated that there were higher RDW and CRP levels with Behçet's disease than in a group of controls. Studies on MPV have mainly concentrated on psoriasis …”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, Kilic et al evaluated MPV in 247 individuals including 116 patients with psoriatic arthritis, 41 patients with psoriasis vulgaris, and 90 healthy controls and reported that MPV was higher in the patients with psoriatic arthritis and patients with psoriasis vulgaris compared to the controls. The authors noted that MPV can be a novel marker of psoriasis (14). Kim et al evaluated 176 patients with psoriasis and 101 healthy controls and reported that MPV was higher in the patients compared to the controls, particularly in those with a high PASI score.…”
Section: Discussionmentioning
confidence: 99%